Oceans'10 Ieee Sydney 2010
DOI: 10.1109/oceanssyd.2010.5603851
|View full text |Cite
|
Sign up to set email alerts
|

Fiber laser sensor hydrophone performance

Abstract: Distributed feedback fiber lasers (DFB-FL) offer potential as a new generation of sensing devices that are inherently small diameter, very sensitive and which can be interrogated over long distances over extremely thin lead in cables. They also have the advantage of requiring minimal or no electronics and thus have the potential to be very robust and reliable.Thales Australia, in collaboration with Defence Science and Technology Organization -Maritime Operations Division, has undertaken the development of a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…5 This acoustic pressure P acts like a longitudinal strain on the Bragg Grating of the DFB FL via the equation…”
Section: The Deep Sea State Zeromentioning
confidence: 99%
See 1 more Smart Citation
“…5 This acoustic pressure P acts like a longitudinal strain on the Bragg Grating of the DFB FL via the equation…”
Section: The Deep Sea State Zeromentioning
confidence: 99%
“…DFB FLs are particularly suited for compact hydrophones array due to their low diameter hydrophone capability and their simple multiplexing capability when they are in series on a single fiber. 4,5 However cascading them may create unwanted external optical feedback in each laser cavity. These external reflections from the side lobes of adjacent Bragg gratings (adjacent with respect to the wavelength) and from Rayleigh scattering in the connecting fiber may result in excess intensity and frequency noise as well as occasional self-pulsing.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to optical interferometric hydrophone technology, emerging Distributed FeedBack (DFB) fiber laser hydrophone technology presents key advantages such as compactness and reduced complexity interrogation scheme [2,3,4,10]. High performance hydrophone design [8,9] associated with optimized DFB fiber laser cavity for dense hydrophone multiplexing capability on a single optical fiber [13] remains a key challenge for this promising new acoustic array technology.…”
Section: Introductionmentioning
confidence: 99%
“…Hence as the curing process progresses the wavelength tends to shift from its designed value before settling into a new final value at the completion of the curing process. 8 It has also been observed that the strains developed during curing process sometimes results in the damage of the grating structure and thereby destroying the sensor itself. 4 The third aspect to be considered when designing the encapsulation is the safe operating depth of the sensor system which often calls for the use of a pressure compensation system that would null the effect of static pressure on the sensor.…”
Section: Introductionmentioning
confidence: 99%